2013
DOI: 10.1016/j.repc.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Hipercolesterolemia – uma patologia com expressão desde a idade pediátrica

Abstract: It is possible to maintain a normal lipid profile in most individuals with familial hypercholesterolemia in order to reduce the risk of early onset of atherosclerosis, which is associated with serious cardiovascular complications from childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Different brown algae species have showed the capacity to lower blood lipid levels and total cholesterol, as demonstrated in numerous different studies [52][53][54][55][56]. In the case of the polysaccharides isolated from brown algae, it has been demonstrated that these compounds essentially affect cholesterol absorption by increasing cholesterol excretion [23,55,68]. As for phlorotannins, different reports demonstrated that its effect in lowering cholesterol is not only because it affects the absorption and excretion of cholesterol, but also because it affects its biosynthesis [84,88].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different brown algae species have showed the capacity to lower blood lipid levels and total cholesterol, as demonstrated in numerous different studies [52][53][54][55][56]. In the case of the polysaccharides isolated from brown algae, it has been demonstrated that these compounds essentially affect cholesterol absorption by increasing cholesterol excretion [23,55,68]. As for phlorotannins, different reports demonstrated that its effect in lowering cholesterol is not only because it affects the absorption and excretion of cholesterol, but also because it affects its biosynthesis [84,88].…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body cholesterol homeostasis is a tightly regulated process that involves de novo biosynthesis, dietary cholesterol absorption, and biliary clearance and excretion [16,22]. An imbalance of these processes may lead to hypercholesterolemia, which is characterized by high levels of total cholesterol (Tc), low-density lipoprotein cholesterol (LDL-c), or triglycerides (TGs), and/or a decrease in high-density lipoprotein cholesterol (HDL-c) [23].…”
Section: Hypercholesterolemia and The Actual Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a significant number of FH patients are not diagnosed and treated in a timely manner. Foreign research has shown that early diagnosis and intervention can delay the occurrence of complications of atherosclerosis and coronary heart disease in FH patients [20][22]. Traditional screening for FH mutations is also infeasible because distribution of the mutation sites is scattered.…”
Section: Discussionmentioning
confidence: 99%
“…Um dos fatores de risco de maior relevância para este grupo de doenças cardiovasculares é a hipercolesterolemia, associada ou não aos outros fatores relevantes de risco cardiovascular como a hipertensão arterial, o tabagismo, o alcoolismo, o excesso de peso e o sedentarismo, entre outros fatores de risco. A hipercolesterolemia resulta do aumento dos níveis de colesterol total no sangue, superior a 200 mg/dL de sangue, em resultado da alteração do metabolismo das lipoproteínas que transportam o colesterol podendo ser de origem comportamental, no que diz respeito aos hábitos alimentares, ou ser de origem genética (Espinheira, et al, 2013). Devido à elevada prevalência e incidência da hipercolesterolemia na população mundial têm sido realizados vários estudos, pesquisas e campanhas de sensibilização para o incentivo à adoção de bons hábitos alimentares, à prática de atividade física e à monitorização regular dos níveis de colesterol no sangue, pois estas medidas são fundamentais para a redução do risco cardiovascular e consequente diminuição da incidência de complicações cardiovasculares (Abreu, 2012).…”
Section: Introductionunclassified